(untitled) (Fiep Bulletin - online, 2011)
This article analyzes, from the thought of Theodor W. Adorno, in some texts of his book "Education and Emancipation," the question of the sport, thinking this as a training body, while the social apparatus, as a possible alternative to stop the savagery the conscience of the individual as object and content of physical education . The spring sports as an important disciplinary device and body conformation, in the same sense of certain productivity, being more used as a vehicle for the dissemination of body movement in elementary school and high school, more than that, are reduced, most often in sports like football, basketball, volleyball and handball are part of the content of physical education classes. Physical education is moving in both a means and an end to achieve their educational objectives within the school context. The sports emerge as an important disciplinary device and body conformation, in the same sense of certain productivity. The sport worked in a school without critical analysis as the notes that Adorno did, has aspects that we find in capitalist society, such as: competition, efficiency, technique, aggressiveness, respect the rules, and other cultural industries. He is distinguished by a major place in the utopia of education and enlightenment. Current trends of physical education in Brazil are close to the thinking of Critical Theory by issues such as on promoting a practice grounded in pedagogical reflection, reflective practice, reflections, critiques that assume a central role in setting up a force resistant to the mechanisms of capitalist reproduction. The idea is already present in the writings of Adorno (2006) claimed that the need for cultural training, and only that, as an element that would condition to counter "pseudo-education" broadcast by semiculture "rooted in the cultural industry.